Do Hertzsprung‐gap stars show any chemical anomaly?. Issue 5 (20th June 2019) - Takeda, Yoichi; Jeong, Gwanghui; Han, Inwoo
Abstract: With the aim of investigating how the surface abundances of intermediate‐mass stars off the main sequence (evolving toward the red‐giant stage) are affected by the evolution‐induced envelope mixing, we spectroscopically determined the abundances of Li, C, N, O, and Na for selected 62 late A through G subgiants, giants, and supergiants, which are often called "Hertzsprung‐gap stars, " by applying the synthetic spectrum‐fitting technique to Lii 6708, Ci 5380, Ni 7460, Oi 6156–8, and Na i 6161 lines. A substantially large star‐to‐star dispersion (≳2 dex) was confirmed for the Li abundances, indicating that this vulnerable element can either suffer significant depletion before the red‐giant stage or almost retain the primordial composition. Regarding C, N, O, and Na possibly altered by dredge‐up of nuclear‐processed products, their abundances turned out to show considerable scatter. This suggests that these abundance results are likely to suffer appreciable uncertainties, the reason for which is not clear but might be due to some kind of inadequate modeling for the atmospheric structure. Yet, paying attention to the fact that the relative abundance ratios between C, N, and O should be more reliable (because systematic errors may be canceled as lines of similar properties are used for these species), we could confirm a positive correlation between [O/C] (ranging from ∼0 to ∼+0.5 dex) and [N/C] (showing a larger spread from ∼0 to ∼+1 dex), which is reasonably consistent with the theoretical prediction. This observational detection of C deficiency as well as N enrichment in our program stars manifestly indicates that the dredge‐up of H‐burning product can take place before entering the red‐giant stage, with its extent differing from star to star.